Cytokine profile in patients with vibration disease, aggravated by hypertension and obesity - N. P. Chistova; G. M. Bodienkova (Медицинская иммунология, 2024)
Comorbid diseases which include arterial hypertension (AH) accompanied by overweight, and vibration disease (VD) are known to contribute to the mutual aggravation of occupational and cardiovascular pathology. Despite numerous studies indicating that some changes of immune system are observed when exposed to vibration, the contribution of cytokines to the comorbid course of vibration disease has not been sufficiently studied. The aim of the work is to evaluate the role of inflammatory mediators in development of hypertension and obesity in vibration disease.The cytokine profile parameters were determined by ELISA immunoassay using “Vector-Best” test systems. Some unidirectional changes in serum cytokine concentrations were found in patients with VD complicatedby AH, and those with VD without AH, being characterized by increase in pro-inflammatory IL-1β, TNFα, IL-17, anti-inflammatory IL-4 and IFNγ, and a decrease in multifunctional IL-2 cytokinem, relative to the comparison group. The groups with versus without AH differed in compensatory increase of anti-inflammatory IL-10 in the latter group. At the same time, all patients with combined VD and AH had excessive body weight, with grade 1 obesity in half of the cases, thus being significantly different from those with VD without AH. It is shown that IL-1β, IL-2, IL-4, IL-8, TNFα play an apparent role in the development of obesity. The greatest contribution is observed for IL-1β, as evidenced by the quantitative relationship of body mass index with its concentrations as assessed by logistic regression analysis. The limitation of this study may be a small sample size.It was found that the unidirectional changes in cytokines when compared to the comparison group were revealed in patients with VD complicated by AH, and in patients with VD without AH. In the subjects with VD and AH, these changes were more pronounced, which may suggest the hypertension is an aggravating factor. The established relationship between individual cytokines (IL-1β, IL-2, IL-4, IL-8, TNFα) and BMI indicates their participation in development of obesity. All these findings may provide a basis for development of preventive and therapeutic measures that reduce the risk of hypertension and obesity in the people working under permanent exposure of vibration.